Pinpoint Loading Examinations of Poly(lactic acid) Biopolymers - Luca Kotrocz; Péter Bakonyi (Acta Technica Jaurinensis, 2018)
We have made a new mounting unit for Dynamic Mechanical Analysis (DMA) equipment, suitable for measuring microhardness and indentation, and examined its usability on thermoplastic poly(lactic acid) (PLA) material.  We used a Vickers-type microhardness indenter, and examined the dimensions of the indented area and the loading force. This novel unit is suitable for measuring the short and long-term behavior of the material using pinpoint load not only at room temperature (20-23 °C) – like common hardness tests – but at a wide range of temperatures.